Integrated wireline log and seismic attribute analysis for the reservoir evaluation: A case study of the Mount Messenger Formation in Kaimiro Field, Taranaki Basin, New Zealand - Haque, A.E. (Elsevier B.V., 2022)
The Early Miocene Mount Messenger Formation, which represents a sand turbidite system, is the primary reservoir of the Kaimiro Field in the Taranaki Basin of New Zealand. The present study integrates the available well log and seismic attribute analyses to identify the prospective horizons' petrophysical characteristics and map them to improve understanding the reservoir characteristics. The seismic volume and well log data were imported into the Petrel 2014 software. The subsurface stratigraphic subdivisions are interpreted till 1000 ms (two-way time travel data) with the available wireline log and 3D seismic data. The workflow characterized the reservoir formation with its lithofacies architecture and interpreting its depositional evolution. The findings from the well log analysis are based on a set of charts designed by cross-plotting the various well log data against each other. These charts indicate that the reservoir comprises sandstone with some shale intercalations and also defined the boundaries between the gas sand and shale zones. The petrophysical analysis revealed that Mount Messenger is characterized by fair to good effective porosity (up to 20.5), shale volume up to 21.4, and hydrocarbon content up to 61. The analyses of strata architecture and lithofacies distributions have provided the overall understanding of the subsurface reservoir sand bodies within the studied sequence. Four types of lithofacies, along with their depositional mechanisms, are identified in the study. Seismic attributes like RMS Amplitude, Half Energy and Mean Amplitude helped quantify the reservoir property of interest. The contour maps developed from the RMS, Half Energy and Mean amplitude showed the presence of significant reservoir zones i.e., 16.1, 15.8 and 4, within the Mount Messanger Formation. Furthermore, the identification of the Channel-Levee Complex is also established by using seismic geomorphology. The study can be extended to conduct detailed field-scale analysis can be further implied on a global scale. Â© 2022 Elsevier B.V.